The crisis of a Public Utility Jeepney operator in the new normal: creating business operational strategies - Caraig, Friderick F.; Andamun, Ashema C.; Roxas, Kervin Owen O.; Dela Torre, Ma. Margie T. (b)
A public utility jeepney (PUJ) is a traditional jeepney in the Philippines. It was known as the "king of the road" and tlie most popular public transportation due to its convenience, accessibility, and lower fare. When the novel coronavirus disease (C0VID-19) pandemic outbreak in the-Philippines and the government placed Metro Manila in lockdown. One of the most affected is a traditional jeepney, the business operation suddenly stopped when the government banned the traditional jeepney on the road. The impact of the COVTD-19 pandemic on jeepney operators is loss of income, loss of passengers, and jobs because one of the: primary sources of income for jeepney operators is their jeepney. Due to implemented health protocols by the government, jeepney operators have a hard time coping with unusual circumstances because of changes in income that result in difficulties sustaining the components, registration of the jeepney, and also the everyday expenses of jeepney operator families. A qualitative case study was conducted in this research paper to investigate how PUJ operators operate their businesses. In terms of data collection, the researchers devised a list of questions to be asked during an online interview with the informants. The researchers' recommendation to the study is to reconceptualize PUJ with a concept of a new face of PUJs by redesigning the passenger{92}s seats and drivers, the placement of the door, modifying the mode of payment, and implementing a color-coding scheme for PUJ to continually operate the business in every business condition. The researchers believe that this output will benefit jeepney operators, drivers, passengers, and the transportation industry to help improve the traffic flow and to have organized, peace, and order within the city. Furthermore, to be more comfortable, safe, and secure especially since we are having our new normal conditions.
Undergraduate thesis.
Keywords: public utility jeepney operator; crisis; strategies; new normal; case study